A screening method of uranyl extractants in H2SO4 solutions. Issue 2 (8th January 2015) - Pasquier, S.; Vercouter, T.; Taran, F.; Lamouroux, C.; Plancque, G.; Berthet, J.-C.
Graphical abstract: Highlights: Selective complexing agents of U(VI) are at the basis of uranium recovery processes. A screening method was developed for identification of U(VI)-selective molecules. Series of mono and bisphosphonate molecules were examined. Their affinity for U(VI) and Fe(III) was assessed in acidic conditions by our method. Two molecules out of fifty-one were found to be of potential interest. Abstract: A UV–Vis spectrophotometric and colorimetric screening method was developed for the selection of powerful and selective ligands for the uranyl ion in sulfuric acid media. The coordinating properties of a series of molecules (mono and bisphosphonate) toward UO2 2+ were examined through ligand displacement reactions observed by UV–visible from the ArzH4 –UO2 2− reference complex where Na2 ArzH6 is a chromogenic molecule displaying a strong affinity for uranium. Uranium/iron selectivity was evaluated by recovering the screening data from two independent sets of experiments using two different chromogenic chelates: arsenazo III for uranium(VI) and BrPADAP for iron(III). As a result, two bisphosphonate ligands among a set of more than 50 phosphonate molecules were found to display a good affinity for UO2 2+ and relevant U/Fe selectivity at pH = 2.1.